More rapid blood interferon α2 decline in fatal versus surviving COVID-19 patients - Joly, Candie; Desjardins, Delphine; Porcher, Raphael; Péré, Hélène; Bruneau, Thomas; Zhang, Qian; Bastard, Paul; Cobat, Aurélie; Resmini, Léa; Lenoir, Olivia; Savale, Laurent; Lécuroux, Camille; et al. (Frontiers in Immunology, 2023)
Background The clinical outcome of COVID-19 pneumonia is highly variable. Few biological predictive factors have been identified. Genetic and immunological studies suggest that type 1 interferons (IFN) are essential to control SARS-CoV-2 infection. Objective To study the link between change in blood IFN-α2 level and plasma SARS-Cov2 viral load over time and subsequent death in patients with severe and critical COVID-19. Methods One hundred and forty patients from the CORIMUNO-19 cohort hospitalized with severe or critical COVID-19 pneumonia, all requiring oxygen or ventilation, were prospectively studied. Blood IFN-α2 was evaluated using the Single Molecule Array technology. Anti-IFN-α2 auto-Abs were determined with a reporter luciferase activity. Plasma SARS-Cov2 viral load was measured using droplet digital PCR targeting the Nucleocapsid gene of the SARS-CoV-2 positive-strand RNA genome. Results Although the percentage of plasmacytoid dendritic cells was low, the blood IFN-α2 level was higher in patients than in healthy controls and was correlated to SARS-CoV-2 plasma viral load at entry. Neutralizing anti-IFN-α2 auto-antibodies were detected in 5% of patients, associated with a lower baseline level of blood IFN-α2. A longitudinal analysis found that a more rapid decline of blood IFN-α2 was observed in fatal versus surviving patients: mortality HR=3.15 (95% CI 1.14–8.66) in rapid versus slow decliners. Likewise, a high level of plasma SARS-CoV-2 RNA was associated with death risk in patients with severe COVID-19. Conclusion These findings could suggest an interest in evaluating type 1 IFN treatment in patients with severe COVID-19 and type 1 IFN decline, eventually combined with anti-inflammatory drugs.